Determining the effective rubrics in the development of a Department Specific CV for hospitality practitioners - Alfaro, Anna Marie Divine E. Amisola, Viema Joceppine L. Caballes, Camille Angelica Casela, John Crisdel M. Ontingco, Korina Beatriz M. 4 0 16; 5
NO ABSTRACT.
Undergraduate Thesis: (B.S. in Hotel and Hospitality Management) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2